Disability 4.0: bioethical considerations on the use of embodied artificial intelligence - De Micco, Francesco; Tambone, Vittoradolfo; Frati, Paola; Cingolani, Mariano; Scendoni, Roberto (Frontiers in Medicine, 2024)
Robotics and artificial intelligence have marked the beginning of a new era in the care and integration of people with disabilities, helping to promote their independence, autonomy and social participation.In this area, bioethical reflection assumes a key role at anthropological, ethical, legal and sociopolitical levels. However, there is currently a substantial diversity of opinions and ethical arguments, as well as a lack of consensus on the use of assistive robots, while the focus remains predominantly on the usability of products. The article presents a bioethical analysis that highlights the risk arising from using embodied artificial intelligence according to a functionalist model. Failure to recognise disability as the result of a complex interplay between health, personal and situational factors could result in potential damage to the intrinsic dignity of the person and human relations with healthcare workers. Furthermore, the danger of discrimination in accessing these new technologies is highlighted, emphasising the need for an ethical approach that considers the social and moral implications of implementing embodied AI in the field of rehabilitation.